Protein Intake, IGF-1 Concentrations, and Growth in the Second Year of Life in Children Receiving Growing Up Milk – Lite (GUMLi) or Cow's Milk (CM) Intervention - Amy L. Lovell; Tania Milne; Misa Matsuyama; Rebecca J. Hill; Peter S. W. Davies; Cameron C. Grant; Cameron C. Grant; Cameron C. Grant; Clare R. Wall (Frontiers in Nutrition, 2021)
The relationship of protein intake with insulin-like growth factor 1 (IGF-1) concentrations in well-nourished children during the second year of life is poorly understood. The aim of this study was to explore the effect of a reduced-protein Growing Up Milk Lite (GUMLi) or unfortified cow's milk (CM) on protein intake, growth, and plasma IGF-1 at 2 y. An exploratory analysis of a sub-sample of Auckland-based children (n = 79) in the GUMLi trial (a double-blind, randomised control trial, N = 160) completed in Auckland and Brisbane (2015–2017) was conducted. One-year old children were randomised to receive a reduced-protein GUMLi (1.7 g protein/100 mL) or a non-fortified CM (3.1 g protein/100 mL) for 12 months. Blood sampling and anthropometric measurements were made at 1 and 2 y. Diet was assessed using a validated food frequency questionnaire. Total protein intake (g/d) from all cow's milk sources was 4.6 g (95% CI: −6.7, −2.4; p < 0.005) lower in the GUMLi group after 12 months of the intervention, with a significant group-by-time interaction (p = 0.005). Length-for-age (LAZ) and weight-for-length (WLZ) z-scores did not differ between groups, however, mean body fat % (BF%) was 3.2% (95%CI: −6.2, −0.3; p = 0.032) lower in the GUMLi group at 2 y. There was no difference between the intervention groups in relation to IGF-1 and IGF-BP3 (p = 0.894 and 0.698, respectively), with no group-by-sex interaction. After combining the groups, IGF-1 concentration at 2 y was positively correlated with parameters of growth (all p < 0.05), total cow's milk intake (p = 0.032) after adjusting for sex, breastfeeding status, and gestation. Randomisation to a reduced protein GUMLi resulted in small reduction in %BF and lower total protein intakes but had no effect on growth. Plasma IGF-1 concentrations were independently associated with total protein intake from cow's milk at 2 y, highlighting a potential area of the diet to target when designing future protein-related nutrition interventions.Clinical Trial Registration: Australian New Zealand Clinical Trials Registry number: ACTRN12614000918628. Date registered: 27/08/2014.